Balkan peninsula as the area of military operation during Balkan wars. Geographical-military characteristics - Krzak, Andrzej (Balcanica Posnaniensia. Acta et studia, 2012)
The Balkan peninsula on account of its peculiar location and the terrain constitutes the unusually interesting object of the research on military conflicts. Forms of operations applied in conflicts, which took place in the range border of the geographical-political Balkans, let read wars run in this area in the course of a few hundred years. Based on experience resulting from the conflicts of Balkan and other antagonisms, which occurred on the Peninsula during the last century, it is possible to state that the conducted research on meaning of this area can constitute the initial base to next research on Balkan military conflicts. Furthermore, the terrain and its components always serve as a toll to pinpoint the indispensable measures to conduct the wars.